Advances in mathematical modeling for reliability - Bedford, T. (IOS Press, 2008)
Discusses fundamental issues on mathematical modeling in reliability theory and its applications. Beginning with a discussion of graphical modeling and Bayesian networks, this work then focuses on repairable systems. It also addresses how competing risks arise in reliability and maintenance analysis through the ways in which data is censored.
Keywords: Engineering : Mathematical models : Congresses; Reliability (Engineering) : Congresses